Polarimetric thermoacoustic imaging - Jiawei Long; Zheng Liang; Yihang Tu; Shimeng Xie; Lin Huang; En Li (Journal of Innovative Optical Health Sciences)
Thermoacoustic imaging (TAI) contrast comes from different electrical properties (EPs) of microwave absorption. However, the relationship between the permittivity distribution and the electric field polarization limits the application of TAI in some extent. Here, we present a polarimetric thermoacoustic imaging (pTAI) system based on a rotary waveguide. By optimizing a rotary waveguide (insertion loss < 0.2[Formula: see text]dB, return loss > 15[Formula: see text]dB at 3[Formula: see text]GHz), the excitation wave emitted from a horn antenna can rotate freely in the direction of polarization. The multi-polarization pulsed microwave signal is used to evoke the thermoacoustic signals (TAS) of samples in different polarimetric directions. The simulation for pTAI with a multi-directional sample is first obtained. Then, we rotated the rotary waveguide at 10∘/s and experimentally demonstrated the performance of pTAI by imaging three randomly placed soy sauce tubes and ex vivo beef. This study suggests that pTAI has potential for dielectric properties “diffusion” mapping, for example, provides conductivity tensor mapping of brain and muscle.